Soils & Fertilizers for Master Gardeners: Soil Drainage and Water Holding Capacity - Amy L. Shober (EDIS, 2009)
Revised! SL-272, a 3-page illustrated fact sheet by Amy L. Shober, helps homeowners understand the natural water status of local soils, allowing them to make decisions about plant selection and irrigation needs. It is part of a series entitled Soils and Fertilizers for Master Gardeners. Includes references. Published by the UF Department of Soil and Water Science, January 2009.